3-D single- and dual-polarized frequency-selective rasorbers with wide absorption bands based on stepped impedance resonator - Wang, Yihao (2021)
A 3-D frequency-selective rasorbers (FSR) with wide absorption bands at both sides of the transmission window based on stepped impedance resonator (SIR) is presented and investigated in this paper. The proposed FSR features thin thickness, wide absorption bands and lumped-element-free characteristics. The transmission channel is constructed from a parallel waveguide based on SIR to provide the transmission path and reduce the thickness of the whole structure. The absorption channel is filled with magnetic absorber to provide a wide absorption band, while meander-line in shunt connection with the absorber is used to avoid lumped components and to obtain a low insertion loss at the passband. The detailed design concept and analysis are illustrated and the fundamental operating principle of the FSR is demonstrated with the help of an equivalent circuit model (ECM). A design example is provided and it exhibits a passband at 7.1 GHz with a transmission bandwidth of 22.6% for less than 3 dB insertion loss and fractional bandwidth of 128.0% with reflectivity less than -10 dB. Moreover, one dual-polarized FSR is also designed and analyzed to generalize the design strategy. Both single- and dual-polarized prototypes are designed, fabricated, and measured to verify the design concept. Good agreement can be observed between the simulated and measured results.